Embodiment in der Pädagogik. - Eberle, Thomas; Awad, Sarah; Ziegler, Alexander (Empirische Pädagogik, 2021)

Embodiment: I sat, I felt, I performed – Posture effects on mood and cognitive performance - Awad, Sarah; Debatin, Tobias; Ziegler, Albert (Acta Psychologica, 2021)
Previous embodiment findings indicate a relationship between physical posture and mood states, suggesting upright postures induce positive mood states. Findings also showed a relationship between moods and cognitive performance. While positive mood states were found to be related to increased processing speed, negative mood states were associated with higher processing accuracy in cognitive task performance. This implies that posture may affect the aforementioned sub-aspects of cognitive performance via mood states. Additionally, most studies on posture effects rely on explicit posture manipulation. With that in mind, our research explores the effects of implicitly manipulated postures on processing speed and accuracy and whether these effects are mediated by general mood. The results revealed that subjects in our sample (N = 82, M = 23.09 years) who adopted an upright posture showed a more positive general mood (d = 0.50) and higher processing speed (d = 0.42) compared to those in stooped postures. Surprisingly, no differences in processing accuracy were found. There was no evidence of the proposed mediation in our data.
CRIS-Team Scopus Importer:2021-06-25
Keywords: Embodied cognition; General mood; Posture; Processing accuracy; Processing speed

Embodiment - The Underestimated Role of the Body in the Learning Process: Towards a Paradigm Shift in School Pedagogy? - Awad, Sarah (Psychologie in Erziehung und Unterricht, 2022)
In recent decades, a family of theories has developed within cognitive science which assigns the body an essential role in cognitive processes. Classified under the concept "embodiment", it is argued that cognitive processes are not primarily located in the brain and solely controlled by it. Instead, it is considered that cognitive functioning is an interplay of body, mind and environment. The comprehension of cognitive functioning is a prerequisite for the optimization of teaching and learning processes. By considering learning and teaching processes against the background of this interaction of body, mind, and environment, beneficial consequences for school learning may result. In this article, theoretical principles and empirical findings on embodiment will be presented and discussed in terms of their potential from a school-pedagogical perspective.
CRIS-Team WoS Importer:2022-08-19

Parental Stress Provoked by Short-Term School Closures During the Second COVID-19 Lockdown - May, Isabelle; Awad, Sarah; May, Matthias; Ziegler, Albert (Journal of Family Issues, 2021)
Governments of numerous countries implemented school closures to contain the COVID-19 pandemic. Several investigations have shown the negative impact of social-distancing policies and school closures on children worldwide. Recently, research also demonstrated adverse effects on adults’ well-being. The development of children is strongly affected by their parent’s emotional state. The present study aimed to examine parental stress levels caused by a short period of homeschooling in December 2020 in Germany. A structured survey was set up and distributed randomly via social media and parent associations. We observed a significant increase in stress and concerns. Family conflicts significantly increased, social isolation was feared, and powerlessness and helplessness ascended. Risk factors were parental education levels, parental working time, and teaching features like the frequency of feedback, correction, and accessibility.
CRIS-Team Scopus Importer:2021-10-22
Keywords: childhood; COVID-19; exposed children; family relations; parental stress